Learning Material Changes as the Impact of the 2013 Curriculum Policy for the Primary School/Madrasah Ibtidaiyah - Prastowo, Andi; Fitriyaningsih, Fitriyaningsih (EDUKASIA, 2020)
Every curriculum change in Indonesia impacts other components in the national education system, including the learning material. However, main material changes have not been discussed completely. This article presents the analysis result about the impact of 2013 curriculum for Primary School (PS) and Madrasah Ibtidaiyah (MI) in Indonesia on the subject materials. This study used a literature review which examined various applicable 2013 policy documents and textbooks as a representation of the core materials. The findings of this study indicate that the change from the 2006 curriculum to the 2013 curriculum in PS/MI level has an impact on changes in teaching material. The structure and method changes are more structured, hierarchical and not overlap among levels, due to core competencies. The presentation is thematic and from concrete to abstract. Material content also changes. Teaching materials in the 2013 curriculum in PS/MI level are contextual, integrative and focused on character and soft skills. Teaching materials in the 2013 Curriculum also covers critical and creative thinking, communicative, and collaborative learning.